Prevalence of Urinary Incontinence in Women (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Objective: The objectives of the study were to find out the prevalence of urinary incontinencein women.Materials and Methods: A cross sectional study was conducted on five hundred one (501)women older than 18 years of age who were admitted in department of obstetrics andgynaecology of Shaheed Suhrawardi Medical College and Hospital from April to December2009, answered a questionnaire about urinary incontinence. They were grouped accordingto presence or absence of urinary incontinence (incontinent and continent) and type ofincontinence present (urge, stress and mixed).Results: Urinary incontinence was found in 104(20.8%) women, out of which 25 (24%)suffered from stress incontinence only, 21 (20.2%) suffered from urge incontinence and58(55.8%) suffered mixed incontinence.Conclusions: One in five women older than 18 years of age suffer from one or other formof urinary Incontinence.Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 59-62